MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN CONTECTUAL TEACHING AND LEARNING SISWA KELAS V SDN 001 RAMBAH - karlina, Karlina (JURNAL PENDIDIKAN ROKANIA, 2018)
This research is a research action (action research). Sub article in this research amount 26 students consist of 12 male students and 14 female students. The focus of this research is learning by using CTL learning model to improve learning outcomes in grade V students of SD Negeri 001 Rambah. CTL learning model proved to improve student learning outcomes Cycle I of the grade average of 79.46% complete and in the second cycle reached 96,74% completeness complete study.